Development of Computer Literacy Courseware for Rural Children using Sarawak Borneo Local Dialects - Syahrul Nizam, Junaini; Subri, S.H. (IEEE Explore, 2012)
In the last decade, computers have become important equipment especially for classroom teaching and help students to learn better. This paper reports the design and development of a courseware to introduce computer literacy for Sarawak rural children. We believe this is the first attempt to create a comprehensive courseware totally in Sarawak Malay dialect and Iban Language. The application is designed in Borneo’s Sarawak Malay dialect and Bahasa Iban. The courseware contains eight learning modules with focus on the topics about basic computer knowledge. In the evaluation stage, we involved students and asked their comments about the courseware. The testing results revealed that using our courseware, the rural children are excited and satisfied to learn basic computer literacy.